Polska Dzikość serca za pięćdziesiąt złotych. Kultura popularna w Zrób mi jakąś krzywdę Jakuba Żulczyka - Małecki, Wojciech (Poznańskie Studia Polonistyczne. Seria Literacka, 2009)
The article presents an analysis of selected functions carried out by the popular cultural references in Żulczyk’s novel Zrób mi jakąś krzywdę, czyli wszystkie gry wideo są o miłości. The first section of the article considers some methodological problems related to the subject matter of the article and discusses the book in view of Shusterman’s aesthetic experience model in the aesthetic legitimization of popular art. The next section includes the analysis of the text and focuses on such issues as references to popular culture in the protagonist’s characteristics. In the conclusion of the article, the author sums up that the popular culture threads are not included in the novel purely for decorative reasons but constitute it at a multi-tiered level and cannot be removed from the novel otherwise it would disrupt, or even destroy, its structure and thus, without some knowledge of the basic elements of pop culture, the reading and understanding of the book can be substantially impaired and incomplete.